Evaluating the nutritional status of preterm very low birth weight infants at discharge: a prospective cohort study - Modi, Poornima; Ramji, Siddharth (International Journal of Contemporary Pediatrics, 2025)
Background: Low birth weight (LBW), defined by the WHO as a birth weight under 2500 grams, is a critical risk factor associated with morbidity and mortality. This study aims to assess the nutritional status of preterm very low birth weight infants at the time of discharge. Methods: This prospective-cohort study was conducted at Maulana Azad Medical College and Lok Nayak Hospital, New Delhi, from April 2009 to March 2010. Results: 80 patients enrolled, comprising 48 males and 32 females. Among the 33 infants (≤32 weeks gestation), 24 completed the study up-to 52 weeks post-conception. Infants born at<32 weeks gestation show significant growth in weight, length and head-circumference by 52 weeks post-conception, yet many fall short of growth standards. Mean weight increased from 1210.4 to 3907 (grams), length from 37.7 to 52 (cm) and head-circumference from 26.7 to 39.5 (cm). A significant proportion remained in the <-3 S.D. category for weight (majority) and length (91.7%), with head-circumference deficits reducing from 21.2% to 12.5%. Conclusions: Exclusive breastfeeding may not reduce the prevalence of extrauterine-growth-restriction in very low birth weight preterm infants, extended follow-up period could show improvements, highlighting a study limitation.